The effect of mild traumatic brain injury on peripheral nervous system pathology in wild-type mice and the G93A mutant mouse model of motor neuron disease. (9th July 2015) - Evans, T.M.; Jaramillo, C.A.; Sataranatarajan, K.; Watts, L.; Sabia, M.; Qi, W.; Van Remmen, H.
Highlights: Mild-TBI did not alter the lifespan of G93A mice or the age of onset. TBI resulted in impaired rotarod performance, grip strength was reduced in TG mice. Electromyography indicates that TBI causes peripheral effects that are increased in G93A mice. Inflammation was detected in the brain and spinal cord by 72 h in WT and G93A mice. Isoprostanes increase in WT spinal cord post TBI to levels comparable to G93A mice. Abstract: Traumatic brain injury (TBI) is associated with a risk of neurodegenerative disease. Some suggest a link between TBI and motor neuron disease (MND), including amyotrophic lateral sclerosis (ALS). To investigate the potential mechanisms linking TBI to MND, we measured motor function and neuropathology following mild-TBI in wild-type and a transgenic model of ALS, G93A mutant mice. Mild-TBI did not alter the lifespan of G93A mice or age of onset; however, rotarod performance was impaired in G93A verses wild-type mice. Grip strength was reduced only in G93A mice after mild-TBI. Increased electromyography (EMG) abnormalities and markers of denervation (AchR, Runx1) indicate that mild-TBI may result in peripheral effects that are exaggerated in G93A mice. Markers of inflammation (cell edema, astrogliosis and microgliosis) were detected at 24 and 72 h in the brain and spinal cord in wild-type and G93A mice. Levels of F2 -isoprostanes, a marker of oxidative stress, were increased in the spinal cord 24 h post mild-TBI in wild-type mice but were not affected by TBI in G93A mice. In summary, our data demonstrate that mild-TBI induces inflammation and oxidative stress and negatively impacts muscle denervation and motor performance, suggesting mild-TBI can potentiate motor neuron pathology and influence the development of MND in mice.